Rocket propulsion elements - Sutton, George P. 1920-; Biblarz, Oscar (John Wiley & Sons Inc., 2017)
Combining fundamental concepts with industry applications, this unique book provides a practical introduction to rocket propulsion principles, mechanisms, and design as applied to guided missiles, space flight, satellite flight, and more. --